Challenges in dissimilar friction stir welding of aluminum 5052 and 304 stainless steel alloys. Issue 6 (12th June 2020) - Chitturi, V.; Pedapati, S.R.; Awang, M.
Abstract: In this study, dissimilar friction stir welding of aluminum 5052 and stainless steel 304 has been carried out with different process parameters. This investigation provides a better insight regarding the defect formation of the weld joints with tilt angles ranging from 0 ° to 2.5 °. The experiments were conducted according to Taguchi L9 orthogonal array by changing the tool rotational speed, and welding speed. The tool pin was kept 70 % towards the aluminum with the tool rotational speed ranging from 800 min −1 to 1200 min −1 with a varying traverse speed of 5 mm/min to 15 mm/min. The bottom part of the stir zone was perfectly welded without any defects. Tunnel defect was detected just above the bottom welded surface. Microstructural analysis reveals that the weld between both materials is formed on the retreating side, whereas on the advancing side, the weld was formed with void defects. Mostly, the stir zone is filled with irregular shaped aluminum and steel parts which were detached from the base material. Several other defects such as voids, cracks, and fragmental defects were observed in the stir zone irrespective of the process parameters. It was observed from the experimental investigations that the tunnel defect can be reduced by increasing the tilt angle. Abstract : Dissimilar friction stir welding of 5052 aluminum and 304 stainless steel alloys was studied. The tool pin was kept 70 % towards the aluminum with the tool rotational speed ranging from 800 min −1 to 1200 min −1 with a varying traverse speed of 5 mm/min to 15 mm/min. This investigation provides a better insight regarding the defect formation of the weld joints with tilt angles ranging from 0 ° to 2.5 °.